2014
DOI: 10.1684/mst.2014.0298
|View full text |Cite
|
Sign up to set email alerts
|

Campaigns for HIV testing, an effective strategy for universal access to prevention and treatment? The experience of Burkina Faso

Abstract: Objectifs l’augmentation du taux de personnes qui connaissent leur statut VIH est un impératif, notamment en Afrique subsaharienne, ce qui impose d’évaluer les stratégies utilisées pour accroître la fréquentation des services de dépistage. Cet article vise à faire le bilan de la pertinence, de la faisabilité et de l’efficacité des campagnes nationales de dépistagemenées entre 2006 et 2010 au Burkina Faso. Méthodologie une analyse de toutes les données de fréquentation du conseil dépistage sur cette période a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Related to the gender, our population was mainly composed of women which is similar to the structure of the general population in Burkina Faso [7]. Somé et al reported a considerable number of women in fixed sites [2]. This was also noted by Biadglegne et al [8] from Ethiopia and Dagnan et al [9] from Côte d'Ivoire who respectively recorded 56.4% and 6 times more HIV-positive women.…”
Section: Evolution Of Clients' Profile At the Centresupporting
confidence: 71%
See 4 more Smart Citations
“…Related to the gender, our population was mainly composed of women which is similar to the structure of the general population in Burkina Faso [7]. Somé et al reported a considerable number of women in fixed sites [2]. This was also noted by Biadglegne et al [8] from Ethiopia and Dagnan et al [9] from Côte d'Ivoire who respectively recorded 56.4% and 6 times more HIV-positive women.…”
Section: Evolution Of Clients' Profile At the Centresupporting
confidence: 71%
“…From 1996 to 2000 where there was a predominance of men and more women from 2001 to 2014, that could be explained is the fact that, since 2000, the national policy for HIV control gives more opportunities to women for counselling relating to the voluntary HIV screening, especially during prenatal visits. In addition, women tend to get themselves tested as part of a fixed strategy compared to men [2]. The education rate in our study (78.3%) was higher than that of the general population (26.8%) [7].…”
Section: Evolution Of Clients' Profile At the Centrementioning
confidence: 70%
See 3 more Smart Citations